2020
DOI: 10.7759/cureus.10136
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Cementless Total Hip Arthroplasty in Avascular Necrosis of the Hip: A Prospective Study

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The final follow-up evaluation for HHS resulted in an improvement to 96.3 (64 out of 100 points). Additionally, Karimi et al (18) HHS was reported to be 100% in 27 (90%) patients, 96% in 2 (7%) patients, and 83% in 1 (3%) patient. We calculated an HHS average of 99.2%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The final follow-up evaluation for HHS resulted in an improvement to 96.3 (64 out of 100 points). Additionally, Karimi et al (18) HHS was reported to be 100% in 27 (90%) patients, 96% in 2 (7%) patients, and 83% in 1 (3%) patient. We calculated an HHS average of 99.2%.…”
Section: Discussionmentioning
confidence: 96%
“…This is in agreement with Reddy et al (17) who reported that the outcomes for everyone were quite excellent. Additionally, Karimi et al (18) reported that 29 (97%) patients had excellent and only 1 (3%) patient had a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, THA, commonly referred to as hip replacement surgery, is a more extensive procedure used when AVN has caused significant joint damage. The procedure entails the extraction of the affected hip joint, followed by the substitution with a synthetic joint [6]. THA is an effective solution for end-stage AVN, as it can alleviate pain and restore function, enabling patients to regain their quality of life (QOL) [7].…”
Section: Introductionmentioning
confidence: 99%